Hellenistic Jewish literature and the New Testament: collected essays - Holladay, Carl R. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2021)
Cover -- Title -- Table of Contents -- Editors' Foreword -- Author's Preface -- List of Abbreviations -- I. Hellenistic Judaism -- 1. The Portrait of Moses in Ezekiel the Tragedian -- 2. Demetrius the Chronographer as Historian and Apologist -- 3. Preparing a Critical Edition: An Appraisal of H. W. Attridge and R. A. Oden, Philo of Byblos -- 4. Jewish Responses to Hellenistic Culture in Early Ptolemaic Egypt -- 5. The Textual Tradition of Pseudo-Orpheus: Walter or Riedweg? -- 6. Pseudo-Orpheus: Tracking a Tradition -- 7. Acts and the Fragments of Hellenistic Jewish Historians -- 8. Hellenism in the Fragmentary Hellenistic Jewish Authors: Resonance and Resistance -- 9. Paul and His Predecessors in the Diaspora: Some Reflections on Ethnic Identity in the Fragmentary Hellenistic Jewish Authors -- 10. Acts and the Fragmentary Hellenistic Jewish Authors -- 11. Spirit in Philo of Alexandria -- 12. Hellenism, Hellenistic Judaism, and Christian Origins: Pfleiderer and Harnack -- II. New Testament -- 13. New Testament Christology: Some Considerations of Method -- 14. 1 Corinthians 13: Paul as Apostolic Paradigm -- 15. Luke's Use of the LXX in Acts: A Review of the Debate and a Look at Acts 1:15-26 -- 16. The Beatitudes: Jesus's Recipe for Happiness? -- 17. The Beatitudes: Happiness and the Kingdom of God -- 18. Happiness Pursued: What the Beatitudes Have Meant -- 19. Schweitzer's Jesus: Crushed on the Wheel of the World? -- 20. Jesus and His Followers in Galilee: Albert Schweitzer's Reconstruction -- 21. Baptism in the New Testament and Its Cultural Milieu: A Response to Everett Ferguson, Baptism in the Early Church -- 22. The Church of the Spirit, the Spirit of the Church: A Lukan Perspective -- Part 1: The Church of the Spirit -- 23. The Church of the Spirit, the Spirit of the Church: A Lukan Perspective -- Part 2: The Spirit of the Church.